A Generalized Sum-Rate Optimizer for Cooperative Multiuser Massive MIMO Link Topologies - Anderson, Adam L.; Jensen, Michael A. (IEEE access, 2014)
Large-scale, or massive, multiple-input multiple-output (MIMO) systems are typified by the number of antennas contributing to a communication link. This type of link can consist of single nodes with a large number of antennas or a large number of cooperating nodes-each contributing a small number of antennas. Such massive systems naturally lead to link topologies that are not often considered in studies of smaller scale cooperative MIMO scenarios. For this system to be economically practical, each node participating in the massive link likely has limited transmit power capability, and therefore properly limiting the per-node transmit power must be incorporated into the signal processing algorithm. This paper develops a generalized multiuser massive MIMO (G4M) optimization algorithm for colocated or cooperative signaling, subject to any sum-, per-antenna, or per-node power constraint, and that can also accommodate nonlinear precoding and detection and any number of antennas. Using the G4M algorithm, a number of topologies unique to cooperative massive MIMO are described, demonstrating the facility this algorithm provides in optimizing the performance of multiuser massive links with atypical topologies.